A basic quasi-Boolean logic of intuitionistic character. Issue 4 (1st October 2020) - Robles, Gemma
Abstract : The logic B M is Sylvan and Plumwood's minimal De Morgan logic. The aim of this paper is to investigate extensions of B M endowed with a quasi-Boolean negation of intuitionistic character included in 3-valued logic G3 and/or 3-valued logic S5 G 3 . Unreduced Routley-Meyer ternary relational semantics are provided for all the logics defined in the paper.